Variabilidad genética de Anopheles punctimacula s.l. en dos localidades de la zona endémica para la malaria: El Bajo Cauca y Alto Sinú (2014)
ABSTRACT: Anopheles punctimacula s.l. is a locally important malaria vector in Colombia. Despite its epidemiological importance, little is known about its genetic variability in the malaria endemic areas where it is present. Amongthese, El Bajo Cauca - Alto Sinú regions report the highest number of malaria cases in the country. Therefore, the aim of this work was to evaluate genetic variability of An. punctimacula s.l. in two localities of each region, Nechí and Montería. This information will guide the design of targeted and effective vector control measures. Materials and methods Starting with the DNA of 20 An. punctimacula s.l., females, fragments of the mitochondrial gene COI and nuclear CPS-CAD were amplified. Nucleotide diversity, haplotype diversity, genetic structure and gene flow parameters were estimated for the populations. Results Eighteen nucleotide sequences were obtained for each marker with a size of 719 bp for CPS-CAD and 1,158 bp for COI. In the CPS-CAD sequences four polymorphic sites were detected and in COI, six. The genetic structure analyses for CPS-CAD (FST= 0.00054) and COI (FST= 0.00049) indicated lack of genetic differentiation and the Nm values (CPS-CAD= 7,78562; COI= 780,5199), evidenced high gene flow between the An. punctimacula s.l. populations of both municipalities. Conclusions Because of the low population structure detected and the high gene flow between the An. Punctimacula s.l. populations from Nechí and Montería suggest that they are genetically similar.